Social Safety Nets : An Evaluation of World Bank Support, 2000-2010 - Independent Evaluation Group (Washington, DC: World Bank Group, 2015)
Events of the past decade have underscored the vital need for social safety net (SSN) programs in all countries, especially in times of crisis. Many countries have some form of targeted SSN program, especially in high- and middle-income countries, but SSNs are increasingly spreading to the lowest income countries. Over fiscal years 2000-10, the World Bank supported SSNs with $11.5 billion in lending and an active program of analytical and advisory services and knowledge sharing, much of it during the last two years of the decade in response to the food, fuel, and financial crises. Yet the crises also pointed out weaknesses, as many middle-income countries (MICs) found that their poverty-targeted SSNs were not flexible enough to increase coverage or benefits as needed, and low-income countries (LICs) lacked poverty data and systems to target and deliver benefits. Bank support evolved in positive directions over the decade. The Bank began to move from a project-focused approach that emphasized delivery of social assistance benefits toward an approach that focused on helping countries build SSN systems and institutions to respond better to poverty, risk, and vulnerability. Stronger demand for SSN support in MICs led to significantly stronger engagement there than in LICs. However, the recent crisis-related expansion of support included also LICs and permitted initiation of Bank support in 15 new countries. The Bankapos;s support to SSNs throughout the decade has relied strongly on both lending and knowledge sharing to engage clients. Bank support has largely accomplished its stated short-term objectives and helped countries achieve immediate impacts. But to achieve the longer-term goal of developing country SSNs, short-term objectives need to be better defined, effectively monitored, and anchored in a longer-term results framework. Weaknesses in poverty data, program designs, and monitoring indicators need to be addressed to ensure target groups are adequately reached. The Bank made substantial progress over the decade, but key areas of Bank support need strengthening.